2015
DOI: 10.1161/strokeaha.115.009592
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Control and Mortality After Stroke in Hypertensive Patients

Abstract: Background and Purpose-Hypertensive patients with electrocardiographic left ventricular hypertrophy are at increased risk of all-cause and cardiovascular death. Lowering blood pressure (BP) after stroke reduces the risk of recurrent stroke, but recent data suggest that lower systolic BP (SBP) measured 5 years after stroke is associated with increased mortality. Whether lower SBP is associated with increased short-term mortality after stroke in hypertensive patients is unclear. Methods-All-cause and cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…These data support the hypothesis that elevating IGF-1 expression in astrocytes significantly improves stroke outcomes after transient ischemia-reperfusion in middle-aged female SD rats. AAV5 mediatedexpression of hIGF-1 in astrocytes reduced stroke-induced motor while controls experienced a decrease in systolic blood pressure after stroke, which is associated with poorer clinical outcomes and increased mortality in stroke patients (Lin, Ovbiagele, Markovic, & Towfighi, 2015;Okin, Kjeldsen, & Devereux, 2015) especially in the acute period of stroke (Wohlfahrt et al, 2015). These novel findings are in accordance with a growing body of evidence that functional modifications of astrocytes yields major benefits for neurodegenerative diseases (Bajenaru, Zhu, Hedrick, Donahoe, Parada, & Gutmann, 2002;Furman et al, 2012Furman et al, , 2016.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These data support the hypothesis that elevating IGF-1 expression in astrocytes significantly improves stroke outcomes after transient ischemia-reperfusion in middle-aged female SD rats. AAV5 mediatedexpression of hIGF-1 in astrocytes reduced stroke-induced motor while controls experienced a decrease in systolic blood pressure after stroke, which is associated with poorer clinical outcomes and increased mortality in stroke patients (Lin, Ovbiagele, Markovic, & Towfighi, 2015;Okin, Kjeldsen, & Devereux, 2015) especially in the acute period of stroke (Wohlfahrt et al, 2015). These novel findings are in accordance with a growing body of evidence that functional modifications of astrocytes yields major benefits for neurodegenerative diseases (Bajenaru, Zhu, Hedrick, Donahoe, Parada, & Gutmann, 2002;Furman et al, 2012Furman et al, , 2016.…”
Section: Discussionsupporting
confidence: 69%
“…AAV5 mediated-expression of hIGF-1 in astrocytes reduced stroke-induced motor impairment, improved sensory motor performance and preferential transmigration of immune cells associated with protective or anti-inflammatory actions. Additionally, systolic blood pressure was stable after transient MCAo in animals with replenished astrocyte IGF-1, while controls experienced a decrease in systolic blood pressure after stroke, which is associated with poorer clinical outcomes and increased mortality in stroke patients (Lin et al 2015; Okin et al 2015) especially in the acute period of stroke (Wohlfahrt et al 2015). These novel findings are in accordance with a growing body of evidence that functional modifications of astrocytes yields major benefits for neurodegenerative diseases (Bajenaru et al 2002; Furman et al 2012; Furman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous data reporting the association of all-cause mortality with SBP in adults with self-reported stroke of NHNSE 1998–2004, 13 and Hypertensive patients with electrocardiographic left ventricular hypertrophy. 14 Also add information on the association of all-cause mortality with elevated DBP to the available literature on this topic. Our results also highlight the optimal BP targets.…”
Section: Discussionmentioning
confidence: 99%
“…[27,28] Previous studies also imply higher blood pressures were associated with higher incidences of death whereas lower blood pressures correlated with coronary artery disease. [29,30] As a result, it is very important to maintain both, the adequate perfusion pressure and reduce the time of hypotension, especially before recanalization. A previous study has reported that more than 70% of stroke patients had blood pressure greater than 170/110 mm Hg.…”
Section: Discussionmentioning
confidence: 99%